Conceção e Desenvolvimento de um Sistema de Gestão de Investigação, Desenvolvimento e Inovação (SGIDI) - Luís Alberto Moreira Pinto (2017)
Research, development and innovation management, more and more, plays a key role in the organization and development of a company. The conception and implementation of an Information system, designed for this sort of management, brings innumerable benefits to a company such as, the optimization of resources and information, the harnessing of ideas and sharing of knowledge, and global vision of projects planning. Standards play an important role in business activities and due to that importance, over the years, standards have been created with specific rules to the IDI, such as UNE 166002 and in the Portuguese case, the very recent standard NP 4457: 2007. NP 4457: 2007, aims to define the requirements of an effective Research, Development and Innovation (RDI) management system, which guarantees to the company the definition of an innovation policy. The standard describes an innovation model, supported by interfaces and interactions between scientific and technological knowledge, the understanding about the organization and its operation and the market or the society in general. Interfaces are important for an effective management of innovation since, through them, are structured, developed and invigorated, all the skills and competencies, crucial to the development of innovation projects. Internal audits are carried out, in order to establish if the innovation plan complies with the target and to verify whether the requirements of the standard are being practiced. The work described in this paper was developed in Nibble, a company certified by the NP 4457: 2007 standard, which aims to define the requirements of an effective RDI management system and guarantees to the company the definition of an innovation policy. Nibble operates with an incipient information system, using folders and documents, small disjointed applications and google forms, to process the entire cycle of information, from the creation of an idea to the finalization of a project or product. This process is time consuming and inefficient. In order to overcome this problem, it was requested, in the scope of this dissertation, the development of a web tool to unify elements of the IDI, such as projects, interfaces and ideas. The management of ideas gives the company's employees the ability to participate in the creation of value for the company itself, being this practice something recent in the companies and having an innovative connotation. The work was divided into different parts: it started with a bibliographical review, with the goal to have a better understanding of the concepts around a SGIDI, such as the different standards, case studies, technologies, and problem review and solution perspective; another part was the analysis of the problem, throughout the observation in loco of the current methods used by Nibble in managing its IDI; then it was done the modeling of an approximate solution through a description and analysis of the requirements and functional specification; finally with integration tests, it was done the implementation and development of the web tool. For the technologies was used the Django web-based framework, based on Python, the base languages of a web application, HTML, CSS and JavaScript and a database in MySQL. Monitoring and control of the projects, evaluation of results and the entire chain of interactions will be further streamlined, so as to achieve better performance of business skills and competences, necessary for the economic development. Nibble intends to market a more advanced version of this tool.